Social Services, School and the Climate of Civil Society - Stephan Sting (Social Work & Society, 2007)
In an international perspective cooperation between social services and school has a long tradition. In the German speaking countries we can recognize a historical distance or gap between school and "social pedagogy", but despite this tradition new forms of cooperation are arising since the last few years. This tendency is part of the development of European societies into "knowledge-based societies" where knowledge and cultural capital are becoming ever stricter criteria for participation in society. This puts particular pressure on those adolescents who threaten to fail in the positional competition for educational qualifications. And it tends to the reproduction and reinforcing of social inequalities due to inequalities in education. For that reason in the article the development of school related social services in different European countries is investigated and it is shown that the increasing pressure to qualification and selection in school creates various problems of integration. Social dimensions of education are pointed out delivering starting points for the cooperation of social services in school and opening opportunities for productive forms of coping with differences between family background, informal social environment and educational milieu in school. Particular attention is paid to differences in socio cultural habits, in socio economical opportunities and in collective practices of interaction. A central focus in the contribution is the orientation towards a participative civil society climate relevant for the interaction between teachers and pupils and between professionals and addressees of social services as well. It is a task of future research in school related social services to analyse their institutional structure and their practices of professional interaction and to find out by European and international comparison in which way social services can contribute to the establishing of a participative civil society climate in school.